Flow-induced vibration of high-mass ratio isolated and tandem flexible cylinders with fixed boundary conditions. (May 2021) - Seyed-Aghazadeh, Banafsheh; Anderson, Nathaniel; Dulac, Sarah
Abstract: Flow-induced vibration of a flexible cylinder placed in the wake of a stationary rigid cylinder is studied, experimentally. The flexible cylinder with an aspect ratio of 47 and a mass ratio of 120 was held fixed at both ends and placed horizontally in the wake of the upstream rigid cylinder in the test-section of a subsonic wind tunnel. The dynamic response of the cylinder is studied in both the streamwise (inline) and transverse (crossflow) directions for center-to-center spacing range from 3 to 9 times the diameter of the cylinder. Amplitudes and frequencies of oscillation, as well as flow forces on the cylinder are studied in the reduced velocity range of U ∗ = 3 . 3 − 50 . 3 and the Reynolds number range of R e = 3, 057 –46, 536. The dynamic response observed in this study are presumably the result of two combined phenomena of vortex-induced vibration and wake-interference galloping. Despite the high-mass ratio of the flexible cylinder, higher modes of vibrations up to the fifth mode are excited in both the crossflow and inline directions, owing to the high-flexibility of the cylinder. Both odd and even modes are excited in the crossflow and inline directions. As the separation distance between the cylinders increases, the amplitudes of oscillation increase over a wider range of reduced velocities. Spanwise trajectories of motion are studied and regions along the length of the cylinder that are excited or damped by the flow, i.e., regions with positive and negative flow force coefficient in phase with velocity, are identified. Highlights: A single high-mass ratio flexible cylinder has a mono-frequency VIV response. A flexible cylinder in the wake of a stationary one has a multi-frequency FIV response. Increase in separation distance between the cylinders leads to mono-frequency FIV oscillation. FIV response of the downstream cylinder is influenced by the upstream one, even at large separations.